The features of cerebral permeability and perfusion detected by dynamic contrast-enhanced magnetic resonance imaging with Patlak model in relapsing–remitting multiple sclerosis - Xiong H; Yin P; Li X; Yang C; Zhang D; Huang X; Tang Z (Dove Medical Press, 2019)
Hua Xiong,1,2 Ping Yin,3 Xiaojiao Li,1,2 Chao Yang,1,2 Dan Zhang,1,2 Xianlong Huang,1,2 Zhuoyue Tang1,2 1Department of Radiology, Chongqing General Hospital, University of Chinese Academy of Sciences, Chongqing 400014, China; 2Molecular and Functional Imaging Laboratory, Chongqing General Hospital, University of Chinese Academy of Sciences, Chongqing 400014, China; 3Department of Radiology, The First Affiliated Hospital of Chongqing Medical University, Chongqing 400016, China Objective: To investigate the features of cerebral permeability and perfusion detected by dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) with Patlak model in relapsing–remitting multiple sclerosis (RRMS) and their correlations with Expanded Disability Status Scale (EDSS) scores and disease duration. Patients and methods: Twenty-seven RRMS patients underwent conventional MRI and DCE-MRI with 3.0 T magnetic resonance scanner were enrolled in the study. A Patlak model was used to quantitatively measure MRI biomarkers, including volume transfer constant (Ktrans), fractional plasma volume (Vp), cerebral blood flow (CBF), and cerebral blood volume (CBV). The correlations of MRI biomarkers with EDSS scores and disease duration were analyzed. Results: The MRI biomarkers Ktrans, Vp, CBF, and CBV of contrast-enhancing (CE) lesions were significantly higher (P<0.05) than those of non-enhancing (NE) lesions and normal-appearing white matter (NAWM) regions. The skewness and kurtosis of Ktrans values in CE lesions were significantly higher (P<0.05) than that of NE lesions. No significant correlation was found among the biomarkers with EDSS scores and disease duration (P>0.05). Conclusion: Our study demonstrated the abnormalities of permeability and perfusion characteristics in multiple sclerosis (MS) lesions and NAWM regions by DCE-MRI with Patlak model. The Ktrans, Vp, CBF, and CBV of CE lesions were significantly higher than that of NE lesions, but these MRI biomarkers did not associate with the severity and duration of the disease. The skewness and kurtosis of Ktrans value in CE lesions were significantly higher than that in NE lesions, indicating that these parameters of Ktrans histogram can be used to distinguish the pathology of MS lesions. Keywords: dynamic contrast-enhanced magnetic resonance imaging, Patlak model, multiple sclerosis, permeability, perfusion, histogram